Health in the hills: an analysis of the health-seeking behaviours of people in rural Makwanpur, Nepal - Gabler, L (2013)
Objectives: The overall aim of this research was to describe the health-seeking behaviours (HSBs) of people in rural Makwanpur, Nepal, and to analyse the patient, household, community, health-system, knowledge and illness factors, and the psychological, social and cultural processes which explain these behaviours. Background: Much about the health status of populations and individuals can be understood by studying how people utilise their health services and the factors associated with this utilisation. HSB studies act as a starting point for the planning of health programmes and the structuring of health systems. Nepal, with its shortage of health providers and funding, its low service usage and its pluralistic medical landscape provides an interesting setting in which to examine HSBs. Most health policies in this context have been devised without taking into account the perspectives of the system users. Moreover, limited formal research on this topic has been carried out in this context. Methods: This study involved a mixed-methods, explanatory sequential design consisting of two phases – quantitative data collection followed by qualitative data collection. Quantitative data was collected using a cross-sectional household survey carried out in 2,334 households across ten VDCs in Makwanpur district between April 2011 and August 2011. Households were selected using a random sampling method. The survey asked about care-seeking in response to an acute episode of illness in the previous one month. Qualitative data was collected after the quantitative data using semi-structured household interviews (n=90) in three VDCs between November and December 2012. The Qualitative interviews were designed to compliment the quantitative findings and to determine the explicit factors associated with care decisions. Results: Of the 2,334 households surveyed,46% had at least one episode of illness in the month prior. The majority of illnesses were infectious or parasitic diseases (42%). Of those households experiencing illnesses, 69% chose to seek care outside of the home; 22% used traditional healers, 37% used allopathic providers and 12% opted for pharmacies as a first option. Sixteen did nothing to address their illnesses, sighting geography, finances, workload and lack of severity as the reasons. Regression models revealed that a host of different patient, household, community, illness, health facility and knowledge factors were associated with care decisions depending on the decision, but illness factors had the greatest impact overall on whether or not a household sought some care or care outside of the home, while household level factors had the greatest impact on the type of care sought outside of the home and the length of delays before seeking care. Patient gender had an impact on whether or not allopathic care was used at least once. Qualitative results revealed that health facility factors were also equally important in determining households’ conscious decision-making about specific providers. Conclusions: Overall it appears that people in Makwanpur are not underutilising health services as suspected. Households use certified government providers most frequently to address their illnesses, and do not rely too heavily on traditional healers or informal providers exclusively. The results indicate that while illness and household factors are important, in order to improve HSBs and increase allopathic care utilisation, a focus should be on improving health service delivery rather than on changing HSBs. However, in order to decrease delays in care-seeking, a focus should be made to reduce household-level barriers to care as well.